Prognostic Factors in Early-Stage Leiomyosarcoma of the Uterus. Issue 3 (1st March 2009) - Pelmus, Manuela; Penault-Llorca, Frédérique; Guillou, Louis; Collin, Françoise; Bertrand, Gérard; Trassard, Martine; Leroux, Agnès; Floquet, Anne; Stoeckle, Eberhard; Thomas, Laurence; MacGrogan, Gaëtan
Abstract : Uterine leiomyosarcomas (LMSs) are rare cancers representing less than 1% of all uterine malignancies. Clinical International Federation of Gynecology and Obstetrics (FIGO) stage is the most important prognostic factor. Other significant prognostic factors, especially for early stages, are difficult to establish because most of the published studies have included localized and extra-pelvian sarcomas. The aim of our study was to search for significant prognostic factors in clinical stage I and II uterine LMS. The pathologic features of 108 uterine LMS including 72 stage I and II lesions were reviewed using standardized criteria. The prognostic significance of different pathologic features was assessed. The median follow-up in the whole group was 64 months (range, 6-223 months). The 5-year overall survival (OS) and metastasis-free interval and local relapse-free interval rates in the whole group and early-stage group (FIGO stages I and II) were 40% and 57%, 42% and 50%, 56% and 62%, respectively. Clinical FIGO stage was the most important prognostic factor for OS in the whole group ( P = 4 × 10 −15 ). In the stage I and II group, macroscopic circumscription was the most significant factor predicting OS ( P = 0.001). In the same group, mitotic score and vascular invasion were associated with metastasis-free interval ( P = 0.03 and P = 0.04, respectively). Uterine LMSs diagnosed using standardized criteria have a poor prognosis, and clinical FIGO stage is an ominous prognostic factor. In early-stage LMS, pathologic features such as mitotic score, vascular invasion, and tumor circumscription significantly impact patient outcome.